PERFORMANCE MANAGEMENT –A TOOL FOR HIGHPERFORMANCE WORK CULTURE AT INFOSYS - Ms.Zipporah (The journal of contemporary issues in business and government, 2022)
In performance management individuals share their understanding of contribution to an organizationsgoal. The basic purpose of this paper is to understand whether employees are able to understand suppositions of management or if there is any discrepancy in doing the same. The paper also aims to describe how performance management forms a tool for creating a high performancework culture. This researchpaperfocuses on the impact of performancemanagement on employee and their individual growth. Finally it tells how organizationcan give better work environment to employees so that they become productive. It also talks about how important performance management is supposed to be understood by both management and employees so that there is clarity in their expectations. Thus it is very important for an organization to see to it that a high performance work culture is created for growth of the organization. In the present world where competition is too high, it is prominent for a company to concentrate on the skill set of employees so that progress of the employees can be tapped into. A greater responsibility lies on the management of the organization to create a high performance workenvironment so that employee’s progress and finally the organizational objectives are achieved. The study also concentrates on making the organization understand where it is lacking in terms of giving the best of the employees. It helps create transparency where both employee-employer expectations are brought to light for the betterment of the organization in terms of performance.